Gestational diabetes versus pregestational diabetes. Perinatal results. - Cristóbal Torres González; Joselin Moreno Torres; Juan Carlos Pastrana Tapia; Vivian Vázquez Martínez (Medisur)
Fundament: Diabetes Mellitus is one of the most affecting diseases in the development of pregnancy. This greatly depends on the metabolic control achieved, which has demanded several proyects of treatment, thus decreasing the risks that the gestational process carries out. Objective: to compare the perinatal results between the diabetic gestational women and pregestational ones admitted at Cienfuegos Hospital. Method: Comparative study developed at the Gynecological-Obstetric Universitary Hospital from Cienfuegos province, from January to december 2003, including 167 pregnant women with Diabetes mellitus during pregnancy. The variables under study were: type of Diabetes, Márquez Guillén classification about good or bad fetal-maternal prognosis , treatment used, type of delivery, gestational age at labor, newborn weight, prenatal and maternal complication. Results: There was a predominance of gestational diabetes (73, 6 %) over the cases with pregestational diabetes (26,3 %). According to Marquez Guillén classification , the bad fetal-maternal prognosis (X=16.37, p < 0.05), the treatment with diet plus insulin(X=53.5, p < 0.05),abortio(X=32.2, p < 0.05),pre term delivery (X=11, p < 0.05),maternal morbidity (X=36.8, p < 0.05) and perinatal morbidity (X=39.6, p < 0.05) were the most frequent in pregestationaldiabetes than in gestational diabetes.